A Review of Application and Benefits of Thin Spray- On Liners for Underground Rock Support in South African Mines - Jjuuko, S.; Kalumba, D. (Spier Conference Centre, Stellenbosch, Western Cape, 2014)
Thin Spray-on Liners (TSLs), an emerging alternative surface support system for underground rock support with performance characteristics in-between those of shotcrete and wire mesh, are receiving increasing attention from the South African mining industry. Previous rock support trials conducted at South African mines and laboratory sites to determine the reinforcement potential of TSLs, and to assess their effectiveness relative to existing traditional support techniques showed positive results. The purpose of this article is to review the reinforcement potential of TSLs surface support system critically in light of the traditional mining technologies. Both laboratory simulations of loose rock deformations and in-situ observation of falls of loose rock fragments, constrained solely by TSL layer strength and rock adhesion were reviewed. An overview of the technology and observed and measured support capabilities is provided and thereafter assessment of rock reinforcement potential done plus the benefits of the technology in the South African mining industry.
Keywords: Rock support; Thin spray-on liners; Shotcrete; Mining; Rockfalls